2001
DOI: 10.1016/s0375-9474(01)01085-5
|View full text |Cite
|
Sign up to set email alerts
|

Meson exchange in the weak decay of Λ hypernuclei and the Γn/Γp ratio

Abstract: We take an approach to the Λ non-mesonic weak decay in nuclei based on the exchange of mesons. The one pion and one kaon exchange are considered, together with the exchange of two pions, either correlated, leading to an important scalar-isoscalar exchange (σ-like exchange), or uncorrelated (box diagrams). Extra effects of omega exchange in the scalar-isoscalar channel are also considered. Constraints of chiral dynamics are used to generate these exchanges. A drastic reduction of the OPE results for the Γ n /Γ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
152
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(170 citation statements)
references
References 57 publications
14
152
4
Order By: Relevance
“…We compare our results with the nuclear matter calculations done in Refs. [26,17]. In the first work a partial wave expansion of the nuclear matter plane waves is done.…”
Section: Calculations IImentioning
confidence: 99%
“…We compare our results with the nuclear matter calculations done in Refs. [26,17]. In the first work a partial wave expansion of the nuclear matter plane waves is done.…”
Section: Calculations IImentioning
confidence: 99%
“…Such a component is two orders higher in the chiral expansion than the corresponding single-pion exchange piece. Also, previous studies [17] found such contributions to be small due to significant cancellations between the correlated and uncorrelated 2 exchanges.…”
mentioning
confidence: 90%
“…The ad-dition of σ and a 1 exchanges does not effectively change the Γ n /Γ p ratio, but proves to be significant in the calculation of the Λ asymmetry parameter as discussed below. Earlier calculations by Jido, Oset, and Palomar (2001), using a chiral-interaction EFT approach, gave a very similar result, Γ n /Γ p = 0.53 in 12 Λ C. Shown also in Table XIII are Λ C, perhaps due to the increased role of the 2N branch which was not included in the calculation. However, earlier calculations using the same exchanges, but with somewhat different couplings and with different prescriptions for the short-range behavior of the OME exchanges, were able to produce values Itonaga, Ueda, and Motoba, 2002;Barbero et al, 2003).…”
Section: Transitionmentioning
confidence: 61%